Exploring Students’ Attitudes and Motivation Toward Project-Based Learning in Speaking Classes: A Study of Third-Semester English Education Students at a University - Jamiatul Khoiriah Hsb; M. Zaim (STAI Hubbulwathan Duri, 2025)
This study investigates the attitudes and motivations of third-semester students in the English Education Study Program at FKIP Universitas Islam Riau (UIR) towards the implementation of Project-Based Learning (PBL) in speaking classes. As PBL becomes an increasingly popular pedagogical method, understanding students' responses is crucial for optimizing its application. A descriptive research design was employed, using questionnaires and interviews to collect data. The study focused on three dimensions of attitude—cognitive, affective, and behavioral—and examined both intrinsic and extrinsic motivational factors. The findings reveal that students generally hold positive attitudes toward PBL. Cognitive attitude received the highest average score (78.77%), followed by affective (77.87%) and behavioral components (75.03%). Motivation levels were also high, with extrinsic motivation (79.40%) slightly exceeding intrinsic motivation (75.97%). These results indicate that PBL fosters both student engagement and motivation in speaking classes. The positive reception suggests that PBL effectively promotes self-regulated learning, collaboration, and practical language use. However, the study also identified challenges, particularly in time management and the need for continuous instructor support. Project-Based Learning is well-received among UIR English Education students and contributes positively to speaking skill development. Future research should include other institutions to enhance the generalizability of findings.